Analysis of global spatial statistics features in existing contrast image quality assessment algorithm - Ahmed I.T.; Der C.S.; Jamil N.; Hammad B.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Higher order statistics; Distorted images; Image quality assessment; Kurtosis and skewness; Lighting conditions; Linear correlation coefficient; No-reference image quality assessments; Spatial statistics; Uneven Contrast; Image quality